The Relevance of Allocation and Distribution of Income in The Islamic Economic Perspective in Indonesia - Hisam Ahyani; Naeli Mutmainah; Memet Slamet (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2023)
The allocation and distribution of a country's income in the 4.0 era need to be given special attention so that it can be allocated efficiently by each individual. The efficiency of allocation and distribution of income in a capitalist economic system has an impact on income inequality in society which can lead to conflict and also creates poverty. But in achieving this prosperity, it is as if there is no government intervention. This study aims to explore how the allocation and distribution of state income are seen from an Islamic economic perspective and also to compare the capitalist distribution system with the Islamic distribution system in the 4.0 era. The research method used is library research which originates from books, journals, the internet, and other relevant sources. The results of the study show that the allocation and distribution of state income from an Islamic economic point of view is an economic concept that has the concept of equal distribution of wealth or income for the community, applicable in Indonesia, which will produce prosperity for the community. The comparison of the capitalist distribution system is based on absolute ownership of the factors of production so that the main goal is to make a profit. As much as possible appears to ignore moral and social values. The Islamic economic distribution system in the era of disruption upholds moral and social values because, in addition to achieving good profitability, Islam also teaches problems in economic activities. With Islamic economic equality, it is hoped that it can reduce the gap in economic inequality to realize prosperity. Therefore, sharia distribution can be carried out by prioritizing Islamic business ethics which is implemented through the concept of Rahmatan lil 'Alamin in the economy. Likewise, in Indonesia, where the majority of the population is Muslim, special attention is needed so that it can implement the allocation and distribution of state income through the concepts of Zakat, Infak, Shadaqah, and Wakaf adapted to the times.